Speciation Distribution of Heavy Metals in Uranium Mining Impacted Soils and Impact on Bacterial Community Revealed by High-Throughput Sequencing - Xiao, Shiqi; Zhang, Qian; Chen, Xiaoming; Dong, Faqin; Chen, Hao; Liu, Mingxue; Ali, Imran (Frontiers in Microbiology, 2019)
This study investigated the influence of heavy metals on bacterial community structure in a uranium mine. Soils from three differently polluted ditches (Yangchang ditch, Zhongchang ditch and Sulimutang ditche) were collected from Zoige County, Sichuan province, China. Soil physicochemical properties and heavy metal concentrations were measured. Differences between bacterial communities were investigated using the high-throughput sequencing of the 16S rRNA genes. The obtained results demonstrated that bacterial richness index (Chao and Ace) were similar among three ditches, while the highest bacterial diversity index was detected in the severely contaminated soils. The compositions of bacterial communities varied among three examined sites, but Proteobacteria and Acidobacteria were abundant in all samples. Redundancy analysis revealed that soil organic matter, Cr and pH were the three major factors altering the bacterial community structure. Pearson correlation analysis indicated that the most significant correlations were observed between the contents of non-residual Cr and the abundances of bacterial genera, including Thiobacillus, Nitrospira, and other ten genera. Among them, the abundances of Sphingomonas and Pseudomonas were significant and positively correlated with the concentrations of non-residual U and As. The results highlighted the factors influencing the bacterial community in uranium mines and contributed a better understanding of the effects of heavy metals on bacterial community structure by considering the fraction of heavy metals.